2007
DOI: 10.1111/j.1742-481x.2007.00351.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy and wound healing

Abstract: This review article discusses basic radiation physics and effects of radiation on wounds. It examines various postulated hypothesis on the role of circulatory decrease and radiation-induced direct cellular damage. The new concept related to the radiation pathogenesis proposes that there is a cascade of cytokines initiated immediately after the radiation. Sustained activation of myofibroblasts in the wound accounts for its chronicity. Recent advances highlight that transforming growth factor beta1 is the master… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 29 publications
1
42
0
Order By: Relevance
“…Because chronic effects can usually be seen 4–6 months after irradiation, a short delay in post-irradiation surgery is recommended to reduce the potential for wound complications [14]. Conversely, the acute effects of irradiation lead to disorders of vascularization and tissue remodeling due to apoptotic cell death; Devalia et al suggested that the surgery should be performed 3 weeks after the completion of radiation therapy [15]. Hence, the safest period for performing surgery after a course of radiation therapy is suggested to be 3–6 weeks after irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Because chronic effects can usually be seen 4–6 months after irradiation, a short delay in post-irradiation surgery is recommended to reduce the potential for wound complications [14]. Conversely, the acute effects of irradiation lead to disorders of vascularization and tissue remodeling due to apoptotic cell death; Devalia et al suggested that the surgery should be performed 3 weeks after the completion of radiation therapy [15]. Hence, the safest period for performing surgery after a course of radiation therapy is suggested to be 3–6 weeks after irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomopathological changes in radiation-induced atherosclerosis have been described and could, besides their impact on clinical outcome, influence the selection of revascularisation strategy in these patients 4. Mediastinal RT is often considered as a contraindication for subsequent CABG owing to extensive scarring and friability of tissues and problematic wound healing 10 18. PCI therefore offers an elegant, less invasive mode of revascularisation, not limited by overt sequelae induced by RT, and its use has been described in case reports or small series to treat radiation-induced CAD with favourable immediate results 19–24.…”
Section: Discussionmentioning
confidence: 99%
“…(15) Ionization of DNA is a direct effect of radiation whereas indirect effects of radiation are mediated through creation of reactive free radicals such as the hydroxide ion, which create the majority of cellular damage. (13) Wound healing has been divided into three stages and takes between one to two years. (15,19,59,62) The first stage consists of hemostasis and inflammation and lasts for about three to four days.…”
Section: Radiation and Wound Healingmentioning
confidence: 99%